1996
DOI: 10.1177/089124249601000405
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of California's Enterprise Zone Programs

Abstract: In 1984, California joined the growing list of states adopting enterprise zone legislation in an attempt to stimulate targeted business development and employment growth within economically distressed areas. This article reports on a first-ever assessment of whether California's two enterprise zone programs have stimulated employment. The existing Enterprise Zone and Economic Incentive Area programs (referred to in the article collectively as enterprise zone programs) have produced very modest economic benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 0 publications
1
67
0
3
Order By: Relevance
“…Sus resultados muestran que no hay efectos significativos en el empleo y en la actividad económica en las municipalidades que tienen beneficios tributarios en zonas geográficas específicas. La evidencia para las zonas industriales y comerciales en California es similar respecto a que no tienen efectos positivos en la generación de empleos (Dowall (1996), Neumark y Kolko (2010)). Finalmente, en un estudio más general que incluye datos para las zonas industriales y comerciales en California, Kentucky, Nueva York, Pennsylvania y Virginia, Bondonio y Engberg (2000) llegan a la misma conclusión, los incentivos tributarios no generan más empleo.…”
Section: Efectos De Los Incentivos Tributarios Localesunclassified
“…Sus resultados muestran que no hay efectos significativos en el empleo y en la actividad económica en las municipalidades que tienen beneficios tributarios en zonas geográficas específicas. La evidencia para las zonas industriales y comerciales en California es similar respecto a que no tienen efectos positivos en la generación de empleos (Dowall (1996), Neumark y Kolko (2010)). Finalmente, en un estudio más general que incluye datos para las zonas industriales y comerciales en California, Kentucky, Nueva York, Pennsylvania y Virginia, Bondonio y Engberg (2000) llegan a la misma conclusión, los incentivos tributarios no generan más empleo.…”
Section: Efectos De Los Incentivos Tributarios Localesunclassified
“…More recently, Dowall (1996) found that most of manner. An EZ located in one part of a city, it is argued, will simply attract capital and jobs away from other parts of the city.…”
Section: The Performance Of Enterprise Zonesmentioning
confidence: 98%
“…The approach taken was 64 similar to that used in Rubin andWilder (1989) andDowall (1996). Also, the rate of growth for the two control areas to be analyzed ( Price, 1994).…”
Section: Job Creation Ana1ysismentioning
confidence: 99%
See 1 more Smart Citation
“…The first Previous studies on state enterprise zones have also used aggregate data on zip codes (e.g., Bondonio and Greebaum, 2007;Dowall, 1996). However, these imprecise approximations may result in a bias towards finding no significant effect (Neumark and Solko, 2010).…”
Section: Data Collection Techniquesmentioning
confidence: 99%